Sosialisasi Pentingnya Berinvestasi pada Pelaku UMKM di Desa Pematang Johar - Revita Sari; Regina Salsabilla (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
Socialization to the community in Pematang Johar Village, Labuhan Deli District, Deli Serdang Regency, North Sumatra regarding the investment we are making with PT Bursa Efek Indo, it is known that although the interest of MSMEs in running a business is very good, in general the knowledge of MSMEs about the law in investment , especially regarding the risks and consequences of investing in funds, in the investment sector it is necessary to provide more in-depth knowledge, it is hoped that with increasing knowledge they will become better than before being given explanations related to investment through lecture methods and discussion forums in socialization activities. The result of this socialization is that the public and MSME players can easily understand the material presented, regarding the explanation of how to invest correctly and how to know whether an honest investment or an illegal investment.